Penyuluhan Manfaat Biskuit Ikan Sori + Kelor Sebagai Pangan Fungsional Pada Balita di Wilayah Pesisir Kota Kendari - Petrus, Petrus; Fatmawati, Fatmawati; Leksono, Purnomo; Abadi, Ellyani; Dwi Putri, Tenri Zulfa Ayu (Karya Kesehatan Journal of Community Engagement, 2024)
Fish + moringa biscuits are a functional local food innovation that is easy to obtain and can be a healthy snack that is rich in nutrients to support the growth of toddlers. The dissemination of the use of fish + biscuits is one of the efforts to increase the knowledge and nutritional status of toddlers. The aim of this service is to increase mothers' knowledge about the benefits of sori fish + moringa made into biscuits. The service method is carried out through lectures and questions and answers. This dedication was carried out on December 19 2023 in Kasilampe Village. The target of this activity is 25 mothers who have toddlers who live in the coastal area of ​​Kasilampe Village. Knowledge data was collected using a questionnaire and analyzed descriptively. The results of this community service are that knowledge before counseling about the importance of fish biscuits + moringa is that 40% of mothers do not understand that moringa biscuits can be given from 6 month old babies and do not understand that fish is an animal protein and after counseling 100% of mothers have know that moringa biscuits can be given from babies as young as 6 months and know that fish is a source of animal protein. The conclusion of this community service was that there was an increase in mothers' knowledge after being given counseling about the benefits of fish biscuits + moringa.